Structurally diverse diterpenoids from Isodon ternifolius collected from three regions. Issue 19 (10th May 2019) - Gou, Lei-Lei; Hu, Kun; Yang, Qian; Li, Xiao-Nian; Sun, Han-Dong; Xiang, Chun-Lei; Puno, Pema-Tenzin
Abstract: Phytochemical investigation of the aerial parts of Isodon ternifolius from three regions in Yunnan Province afforded 9 new diterpenoids, ternifoliusins A–I (1 –9 ), together with 26 known diterpenoids. Among them, ternifoliusins A–D possess rare 6, 7:8, 15-diseco-7, 20-olide-6, 8-cyclo- ent -kaurane diterpenoid scaffold. The structures of all compounds were determined by comprehensive spectroscopic analysis, as well as quantum chemical calculation methods. Moreover, the molecular constitutions and configurations of ternifoliusins A, E, and F (1, 5, 6 ) were confirmed by single-crystal X-ray diffraction analysis. Ten compounds were assayed for their cytotoxic activity against the HL-60, SMMC-7721, A-549, MCF-7, and SW-480 human tumor cell lines, and compounds13, 17, 19, 20, 31 and34 were demonstrated to be active against all of the five human tumor cell lines. Graphical abstract: Image 1 Highlights: Nine new diterpenoids were obtained from Isodon ternifolius. Four of them possess rare ent -kaurane diterpenoid scaffold. All structures including absolute configurations were determined, and those of1, 5, and6 were confirmed by single-crystal X-ray diffraction experiment. Quantum chemical calculation methods were applied in determining the absolute configuration of compounds7, 8 and9. Compounds13, 17, 19, 20, 31 and34 were remarkably active against all of the five human tumor cell lines.